Length-length relationships of elongate glass perchlet, Chanda nama (HAMILTON, 1822) from the old Brahmaputra river, Bangladesh - Aktar, Nelufa; Ahmed, Zoarder Faruque; Fatema, Mst Kaniz (Research in Agriculture Livestock and Fisheries, 2022)
The generalized length-length relationships of Chanda nama ((Hamilton, 1822) belongs to Ambassidae were studied separately for a period of a calendar year collected from the Old Brahmaputra River, Mymensingh, Bangladesh for male, female and combined populations. A total of 1170 specimens were examined where 599 were male and 571 were female. The standard length, fork length and total length of male ranged from 19 to 79 mm, from 23 to 90 mm, and 28 to 100 mm respectively. The standard length, fork length and total length of female were found from 15 to 81 mm, 24 to 89 mm, and from 29 to 100 mm respectively. The generalized relationships of standard length and fork length, fork length and total length, and standard length and total length of male, female and combined populations were FL = 1.08 SL+1.41, TL = 1.11 FL + 1.54 and TL = 1.20 SL+2.81; FL = 1.09 SL+1.23, TL = 1.12 FL+1.04 and TL = 1.22 SL+2.22; and FL = 1.09 SL+1.20, TL = 1.11 FL+1.27 and TL = 1.22 SL+2.38 respectively. The coefficient of determination (R2) revealed high values in all regression analyses. In length–length relationships, the coefficient of determination (R2) ranged from 0.973-0.990. The present findings of this study will be helpful for a well-organized and significant exploitation and regulation of the Chanda nama fishery in the Old Brahmaputra River and surrounding ecosystems. Res. Agric., Livest. Fish.8(3): 339-347, December 2021